2008
DOI: 10.1007/s00423-008-0340-4
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital identification of major trauma patients

Abstract: Background and aims Prehospital triage is aimed at getting the right patient to the right hospital. Evaluations on the performance of prehospital triage tools are scarce. This study examines the ability of the American College of Surgeons' Committee on Trauma (ACSCOT) triage guidelines to identify major trauma patients in a European trauma system. Furthermore, this study evaluates the predictive power of other prehospital measurements. Materials and methods Prehospital data of 151 minor (Injury Severity Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Several retrospective studies have introduced new prehospital triage models to identify major trauma patients in the prehospital setting. However, these models still need to be validated in prospective studies [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have introduced new prehospital triage models to identify major trauma patients in the prehospital setting. However, these models still need to be validated in prospective studies [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a lower compliance rate to the vital sign criteria [23,34,38]. This could be because the majority of the trauma patients have normal or near normal vital signs [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de la atención del paciente en el campo prehospitalario, se han desarrollado varios criterios de triage para determinar la severidad de las lesiones, el modo de transporte y el destino más apropiado para un paciente de trauma. [21][22][23] En este campo el índice de shock ha sido propuesto como un criterio en el Protocolo Nacional de Triage en Trauma en los Estados Unidos para direccionar al el paciente a un Centro de Trauma, mostrando que un valor >1.0 aumenta la sensibilidad con una mínima reducción de la especificidad comparado con una tensión arterial sistólica <90mmHg para identificar a los pacientes inestables que requieren atención de mayor complejidad.…”
Section: Discussionunclassified